Roa And Roe Analysis Of HIMBARA Bank Performance In Cooperation With ATM Merah Putih - Muhammad Ferdy Firmansyah; Axel Giovanni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The writing of this article is to determine the effect of the Red and White ATM on the financial performance of HIMBARA Bank. By using research data from 2016 to 2020. Financial performance is measured by the profitability ratio as seen from the Return On Assets (ROA) and Return On Equity (ROE) ratio. This research is a qualitative research. The data used are financial report data obtained from the respective official websites. The research sample is 4 banks which are included in HIMBARA bank. Data analysis used Paired sample t-test analysis. The results showed that the red and white ATM affects the financial performance of HIMBARA bank.